The History of Ireland's Marine Fisheries, 1500 to 1603 - Hayes, Patrick (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2021)
This thesis illuminates the history of Irish fisheries from 1500 to 1603 by utilising a range of digital research methods. Previous monographs on the history of Irish fisheries have been unfocused and anecdotal. In contrast, this thesis has taken a far more systematic and concentrated approach to the topic. Two central relational databases store and analyse primary source material in this work, one encompassing qualitative information and the other quantitative data. Information derived from qualitative sources illustrates that Ireland played host to a diverse range of fishing operations around 1500, with fishers from across Europe visiting specific Irish coastal regions that had developed complex systems to accommodate and tax these visitors. Foreign fishers who frequently Irish waters would later go on to establish significant fisheries in Newfoundland in the later sixteenth century. Old English towns also had active fishing fleets that operated locally and travelled across Ireland in search of catches. Quantitative trade data shows that fish was Ireland's premier export commodity in the late fifteenth and early sixteenth centuries. However, the industry suffered a dramatic collapse by the end of the sixteenth century. A combination of factors contributed to this decline, including the impact of successive conflicts related to the Tudor re-conquest of Ireland. By 1603, English colonialism fundamentally altered the access and ownership of fishing resources in Ireland and ended the operations of foreign fishing fleets. Finally, this thesis illustrates that favourable climate and ocean conditions likely aided the expansion of Irish fisheries in the mid-fifteenth century, while contrasting poor conditions contributed to the industry's collapse in the later sixteenth century. Ultimately, this study reveals that the importance of early modern fisheries in Ireland has previously been seriously underestimated as regards trade and domestic consumption and that the politics of the period need to be viewed in light of the fisheries' wider economic importance.
APPROVED
Keywords: Marine environmental history; Economic history; Fisheries; Irish history; Early modern history; Historical GIS; Digital humanities